Ergonomic Risk, Muscle Tension, Lactic Acid, and Work Performance on Transport Workers at Fish Auction - Bina Kurniawan; Zen Rahfiludin; Yuliani Setyaningsih; Nurjazuli Nurjazuli (Media Kesehatan Masyarakat Indonesia, 2022)
One of the main occupations in fish auction facilities was transport worker. Manual handling activities are a leading cause of workplace injuries such as strains and back injuries. This study aims to analyze the association between ergonomic posture with muscle tension, lactic acid buildup, and work performance. This study was carried out in November 2020. The instruments in this study were portable electromyography, lactate analyzer, REBA Assessment sheet, and questionnaire. The analysis was performed with statistical test using Fisher Exact Test. This study is analytical survey research with cross-sectional study design with 51 respondents selected using convenience sampling method. Based on the data obtained, it was found that 36 respondents (70.59%) did not work ergonomically. The result of the analysis is that there is an association between ergonomic posture and muscle tension (p=0.000) and lactic acid buildup (p=0.002), but there is no association between ergonomic posture and work performance (p=0.761). It is necessary to improve the quality of fish auction facilities services by providing ergonomic transportation aids such as lifting trolleys and training related to the dangers of ergonomic risk factors at fish auction facilities.